LncBIRC3-OT promotes the malignant progression of glioma by interacting with RELA to upregulate stanniocalcin-1 expression - Renjie Wang; Qi Li; Xiaolei Chu; Nan Li; Haiqian Liang; Feng He (Heliyon, 2023)
Glioma is the most common malignant intracranial tumor, accounting for 80 % of all malignant brain tumors. Growing evidence suggests that lncRNAs are involved in the growth, angiogenesis, metastasis, and therapeutic resistance in a variety of tumors, including glioma. In this study, lncBIRC3-OT (NONHSAT159592.1), which is highly expressed in glioma, was screened by RNA-seq method and verified by quantitative reverse transcription polymerase chain reaction. Subsequently, we knocked down the endogenous expression of lncBIRC3-OT in U87 and U251 cells and found that down-regulated lncBIRC3-OT inhibited cell proliferation, colony formation, migration, and invasion. Mechanically, lncBIRC3-OT could guide RELA protein to the stanniocalcin-1 (STC1) promoter, initiate STC1 transcription, and ultimately promote the progression of glioma. Together, these findings suggest that lncBIRC3-OT is an important regulator promoting glioma progression, and may be a promising therapeutic target for glioma.